Exploring the safety of motorcycles riders in the campus of Universiti Utara Malaysia (UUM) - Melan, Mustakim; Zakaria, Muhammad Salahafiz; Abdullah, Nor Shapira; Soh, Mohamad Nasir (2015)
The increasing number of private vehicle especially motorcycles owned by students is contributing factors to accident in the campus. Investigation shows that attitudes, lacks of efficient road designs and infrastructure that leads to heavy traffics which indirectly caused of the accidents.The objectives of this research are to investigate the motorist attitudes and educate students to ensure their safety in future.The research was conducted through observation and questionnaires that involved with 385 students. Questionnaire was the main instrument for the study and it was gathered and analyzed. Data analysis was conducted by using descriptive analysis (mean and standard deviation),reliability analysis, Pearson correlation analysis and multiple regressions.The findings showed that there were relationships between safety effectiveness as dependent variable and Two (2) independent variables such as motorist attitudes and road design infrastructures.The results of the study are suggested to be used for future guidelines for the university.